Harmful Intent - Cook, Robin, 1940- (New York Pan Books, 1990)
An anaesthetist gives a woman a normal injection during childbirth and she dies. The doctor is sued and criminally charged, but he skips bail and returns to the hospital to try and find out exactly what went wrong. On the run from the police, he uncovers a pattern of similar killings.
Keywords: Physicians -- Conspiracies -- Medical fiction